Pengaruh Ekstrak Bawang Merah dan Zat Pengatur Tumbuh Auksin terhadap Pertumbuhan Setek Mucuna bracteata D.C. - Silvana Prameswari; Bayu Pratomo (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: This study aims to obtain concentration of shallot extract (Allium cepa ) and growth regulators to increase growth of Mucuna bracteata. Mucuna is a land cover plant that must be planted in oil palm plantation areas. It is very important to be able to cover the planting area. Materials and Methods: This study used two factorial in randomized block design. The first was concentration of shallot extract per 100 ml distilled water consists of 4 levels, such as control (B0), 10 cc (B1), 20 cc (B2), 30 cc (B3) and the second was the auxins-plant growth regulator consists of 4 levels: Control (G0), 100 ppm (G1), 200 ppm (G2), 300 ppm (G3). Data analyzed with ANOVA with a significant 5% and continued with the DMRT using SAS version 9.1.3. Results: It was found that effect of concentration of shallot extract had a significant effect on survival percentage of Mucuna bracteata at a concentration of 10 cc (B2) after opening the lid at four weeks after planting (WAP) and did not change until 8 WAP. Likewise, the number of leaves at the control concentration (B0) at the age of 6 WAP, and a concentration of 10 cc (B1) at the age of 7-8 WAP. The concentration of growth regulators and their interactions did not significantly affect the survive percentage and number of leaves in Mucuna bracteata.